Darwin's goldmine is still open: variation and selection run the world - FORTERRE, Patrick (Frontiers in Cellular and Infection Microbiology, 2012)
The scientific contribution of Darwin, still agonized in many religious circles, has now been recognized and celebrated by scientists from various disciplines. However, in recent years, several evolutionists have criticized Darwin as outdated, arguing that “Darwinism”, assimilated to the “tree of life”, cannot explain microbial evolution, or else was not operating in early life evolution. These critics either confuse “Darwinism” and old versions of “neo-Darwinism” or misunderstand the role of gene transfers in evolution. The core of Darwin explanation of evolution (variation/selection) remains necessary and sufficient to decipher the history of life. The enormous diversity of mechanisms underlying variations has been successfully interpreted by evolutionists in this framework and has considerably enriched the corpus of evolutionary biology without the necessity to kill the father. However, it remains for evolutionists to acknowledge interactions between cells and viruses (unknown for Darwin) as a major driving force in life evolution.